Kawasaki Disease: A Single-Center Study from a Tertiary Care hospital in Dhaka, Bangladesh (Bangladesh Journal of Child Health, 2024)
Background: Kawasaki Disease (KD) is recognized as the leading cause of acquired heart disease in children in developed countries. This is a pioneer study from Bangabandhu Sheikh Mujib Medical University (BSMMU), documenting the common epidemiological, clinical, laboratory and echocardiographic findings, including management and immediate outcome of KD children.Method: This retrospective study includes all patients with a diagnosis of KD, who attended the pediatric rheumatology division at BSMMU from January 2015 to December 2019. Data were collected from medical records at diagnosis and immediately after management. Relevant statistical tests were done and a p value < 0.05 was considered as statistically significant.Result: A total of 129 cases were diagnosed with KD, among them complete KD cases were 62% and incomplete KD was 38%. The mean age at onset was significantly higher in incomplete KD than complete KD. The majority of the cases (67%) were between 1 to 5 years of age and male (72%) children were predominant. Fever was the most common presenting feature (100%), followed by bilateral conjunctivitis, mucosal involvement, rash, changes in extremities, cervical lymphadenopathy and others. Coronary artery dilatation was present in 30.5% cases with no significant differences between complete and incomplete KD cases. Aspirin was given to all the cases and IVIG was given to only 46.6% children. Rests of the children were treated with methyl prednisolone. All the cases improved after treatment and there was no immediate mortality.Conclusion: It seems that KD is not an uncommon disease and incomplete KD cases are relatively more prevalent. About 30% KD cases had coronary artery abnormalities. Immediate outcome of management is excellent but needs long term follow-up.BANGLADESH J CHILD HEALTH 2023; VOL 47 (1) : 9-16